Income, Identity, and International Redistribution: Evidence from the European Union - Julian Schüssler; Thomas Hinz; Dirk Leuffen; Peter Selb (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2024)
Previous research emphasizes that individual economic status does not significantly influence support for redistribution within the European Union (EU). Instead, identity factors are often posited as the main causes. We study the interaction of these variables and synthesize various theories that all predict that heightened European identification leads to a weaker influence of economic status. In a large original survey fielded in 12 countries, we find that respondents' income and perceived relative position correlate negatively with their redistribution preferences, both on the national and the EU level, as predicted by economic accounts. We also replicate findings on the positive effect of identity variables and find some evidence for the predicted interaction. However, randomized information treatments aimed at altering perceptions of an individual's or their member state's relative economic position fail to impact on preferences and do not interact with identity variables. Overall, our findings point toward a possible but quantitatively very limited role of economic status and its interaction with identity in understanding EU redistribution preferences.
urn:nbn:de:bsz:352-2-1pyjlb1st83175
Keywords: 320